Practical application of BPM to improve picking process in a logistics distribution center - Santos López, Félix Melchor (2012)
Distribution centers are quite sensitive areas to produce failures due to human mistakes through the picking process. As a result, it impacts enormously the level of service and organization’s goals. The object of study is a drugstore whose number of orders is very high and the number of handled products too. Solution is given as a tool that applies Business Process Management (BPM) and provides characterization of organizational processes, the current picking process diagram (AS-IS) and the improved diagram (TO-BE) which enhances the process adding a new control point. Besides, in this paper BPMN notation was applied correctly in each diagram.